The bionarrative : the story of life and hope for the future - Boyden, Stephen Vickers (ANU Press, 2016)
This book is for the general reader interested in the human place in nature and the future of civilisation. It is based on the biohistorical approach to the study of human situations. This approach recognises human culture as a new and extremely important force in the biosphere. The book discusses the evolution of life and the essential ecological processes on which all life, including human civilisation, depend. It describes the conditions of life and ecology of humans in the four ecological phases in human history, with emphasis on the impacts of human culture on biological systems. It explains how, as cultures evolved, they often came to embrace not only factual information of good practical value, but also assumptions that are sheer nonsense, sometimes leading to activities that caused unnecessary human distress or damage to local ecosystems. These are examples of cultural maladaptation. There have been countless instances of cultural maladaptation in human history. The days of the fourth ecological phase of human history, the Exponential Phase, are numbered. Cultural maladaptations are now on a massive scale, and business as usual will inevitably lead to the ecological collapse of civilisation. The only hope for the survival of civilisation lies in radical changes in the worldviews and priorities of the prevailing cultures of the world, leading to a fifth ecological phase--a phase in which human society is truly sensitive to, in tune with and respectful of the processes of life. This is called a biosensitive society. The book concludes with discussion on the essential characteristics of a biosensitive society and on the means by which the necessary cultural transformation might come about.